A qualitative study of single-trauma and dual-trauma military couples - Goff, Briana S.; Irwin, Laura D.; Cox, Michelle D.; Devine, Sara I.; Summers, Kali J.; Schmitz, Anne E. (My University, 2014)
Trauma survivors and their partners may experience unique dynamics due to the ongoing effects of previous trauma exposure and current trauma symptoms. The current qualitative study attempted to compare and contrast single-trauma couples (one partner reports a trauma history or high traumatic load) with dual-trauma couples (both partners report a trauma history or high traumatic load) to further understand the systemic effects on couple functioning in a sample of military couples. Overall, both positive and negative effects from previous trauma on the couple relationship were reported by participants, including increased awareness, communication, support, coping strategies, and trauma-related triggers, with dual-trauma couples reporting more trauma-related triggers and communication problems. Clinical and research implications for further study are described.
Keywords: Trauma survivors; Single-trauma couples; Dual-trauma couples; Military couples